The effectiveness of using carbonate isotope measurements of body tissues to infer diet in human evolution: Evidence from wild western chimpanzees (Pan troglodytes verus). Issue 88 (November 2015) - Fahy, Geraldine E.; Boesch, Christophe; Hublin, Jean-Jacques; Richards, Michael P.
Abstract: Changes in diet throughout hominin evolution have been linked with important evolutionary changes. Stable carbon isotope analysis of inorganic apatite carbonate is the main isotopic method used to reconstruct fossil hominin diets; to test its effectiveness as a paleodietary indicator we present bone and enamel carbonate carbon isotope data from a well-studied population of modern wild western chimpanzees ( Pan troglodytes verus ) of known sex and age from Taï, Cote d'Ivoire. We found a significant effect of age class on bone carbonate values, with adult chimpanzees being more 13 C- and 18 O-depleted compared to juveniles. Further, to investigate habitat effects, we compared our data to existing apatite data on eastern chimpanzees ( P. troglodytes schweinfurthii ) and found that the Taï chimpanzees are significantly more depleted in enamel δ 13 Cap and δ 18 Oap compared to their eastern counterparts. Our data are the first to present a range of tissue-specific isotope data from the same group of wild western chimpanzees and, as such, add new data to the growing number of modern non-human primate comparative isotope datasets providing valuable information for the interpretation of diet throughout hominin evolution. By comparing our data to published isotope data on fossil hominins we found that our modern chimpanzee bone and enamel data support hypotheses that the trend towards increased consumption of C4 foods after 4 Ma (millions of years ago) is unique to hominins.